ANALISIS PENANAMAN MODAL ASING, INFLASI DAN PENGANGGURAN TERHADAP PERTUMBUHAN EKONOMI DI SUMATERA UTARA - Rusiadi, Rusiadi; Novalina, Ade (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa); Vol 2 No 1 (2017): JURNAL Kajian Ekonomi dan Kebijakan Publik, 2020)
This research aims to analyze the influence of foreign capital investment, unemployment and inflation are partial towards economic growth in Northern Sumatra. Analyse the influence of foreign capital investment, unemployment and inflation simultaneously towards economic growth in Northern Sumatra. Data collection is done the author sourced from data that is in the Official Website of the Central Bureau of statistics of North Sumatra Area, the data in the form of Foreign Direct Investment, investment amount of inflation, the number of unemployed, the amount of GDP in North Sumatra, in a span of 10 years i.e. from 2005-2015. Data analysis using multiple linear regression. The results showed that penenaman foreign capital very significantly affect economic growth, while inflation and unemployment effect is not significantly to economic growth in Northern Sumatra. Simultaneous penenaman of foreign capital, inflation, and unemployment is a significant influence on economic growth in Northern Sumatra.